2015
DOI: 10.1111/apt.13459
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in serotonin metabolism in the irritable bowel syndrome

Abstract: SUMMARY BackgroundAlterations in serotonin (5-HT) metabolism have been postulated to play a role in the pathogenesis of irritable bowel syndrome (IBS). However, previous reports regarding 5-HT metabolism in IBS are contradicting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 69 publications
3
58
2
1
Order By: Relevance
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…[10][11][12][13][15][16][17][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] The baseline characteristics of included studies are shown in Table 1 22,29 Sphere score in 1 study, 24 and the Beck Anxiety Inventory (BAI) in 1 study. 30 …”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…A total of six studies were included. 15,17,18,37,38,65 In those studies, healthy-control groups were used for multiple comparisons with the three IBS-subtypes; we divided the healthy-control group into three groups for meta-analysis of three IBS-subtypes alongside healthy controls. Depression levels were significantly higher in IBS-C (SMD = 0.83; 95% CI, 0.61-1.06; I 2 = 0%; P < 0.001), IBS-D (SMD = 0.73; 95% CI, 0.51-0.96; I 2 = 0%; P < 0.001), and IBS with mixed bowel habits (SMD = 0.62; 95% CI, 0.39-0.84; I 2 = 0%; P < 0.001) (Fig.…”
Section: Depression and Anxiety In Irritable Bowel Syndrome-subtypementioning
confidence: 99%
See 2 more Smart Citations
“…The latter seemed to be associated with duodenal immune activation, with increased numbers of IELs and mast cells being observed, and significant increases in tryptase release. Interestingly, in one study, alterations in 5-HT metabolism in 154 IBS patients did not seem to correlate with GI symptoms, or mood [84]. However, the technical issues of avoiding contamination from platelet release of 5-HT in these studies remain a concern.…”
Section: Evidence For the Role Of Abnormalities In 5-ht Metabolismmentioning
confidence: 99%